Diagnosis of damaged tendons on a 10 MW multibody floating offshore wind turbine platform via a response-only functional model based method. (1st September 2021) - Sakaris, Christos S.; Bashir, Musa; Yang, Yang; Michailides, Constantine; Wang, Jin; Sakellariou, John S.
Highlights: Diagnosis of damaged tendons on a new multibody Floating Offshore Wind Turbine platform. Damage precise quantification in a floating offshore structure's tendons. Diagnosis achieved via a response-only Functional Model Based Method. Accurate diagnosis under a limited number of sensors and low frequency bandwidth. Abstract: The problem of damaged tendon diagnosis (damage detection, damaged tendon identification and damage precise quantification) in a new multibody offshore platform supporting a 10 MW Floating Offshore Wind Turbine (FOWT) is investigated for the first time in this study. Successful operation of the multibody FOWT depends on the integrity of its tendons connecting the upper and lower tanks of the platform. Thus, early diagnosis of the damaged tendons is of high importance and it is achieved through a vibration-based methodology. Damage detection is accomplished based on the detection of changes in the vibration response power spectral density, while damaged tendon identification and damage precise quantification are accomplished through the Functional Model Based Method (FMBM). The FMBM is appropriately formulated in this study to operate with only vibration response signals. The employed vibration responses under healthy and damaged states of the FOWT platform are obtained from a numerical model describing the platform's dynamics. Each examined damage scenario corresponds to the reduced stiffness at the connection point of a single tendon to the platform's upper tank. Subtle damages corresponding to a stiffness reduction of [10–25] %, have minor effects on the platform's dynamics due to the tendons' high strength, while damages corresponding to a stiffness reduction of [10–85] % on different tendons have similar effects on the dynamics, thus leading to an overall highly challenging diagnosis problem. The use of a single underwater accelerometer as well as a low and limited frequency bandwidth of surge acceleration signals, is explored. The results show that effective, reliable and very quick damaged tendon diagnosis is achieved via FMBM using the multibody FOWT platform's dynamics under damaged tendons.